Михайло Драгоманов як поліґістор - Погребенник, В. (Україна: культурна спадщина, національна свідомість, державність, 2012)
Статтю присвячено науковій спадщині М. Драгоманова як поліґістора, його здобуткам
в історичній, філологічній науці тощо. Висвітлено значення його діяльності в Україні й
за кордоном, еволюцію поглядів ученого, актуальність ідей М. Драгоманова у ХХІ ст. The article focuses on the scholarly heritage of Mykhailo Drahomanov as a polyhistor as well as his achievements in history, literature and linguistic studies, etc. The significance of his activities in Ukraine and abroad, the evolution of the scholar’s viewpoints and the topicality of his ideas in the 21th century are highlighted in the article.